SISTEM PENGAMBILAN KEPUTUSAN PERENCANAAN DAN PEMBANGUNAN PEMERINTAH BERBASIS ANALYTICAL HIERARCHY PROCESS (AHP) (STUDI KASUS: MUSRENBANG PEMERINTAH DAERAH KAB. HALMAHERA UTARA) - Batawi, Rymond N.; Sediyono, Eko (Proceedings of KNASTIK, 2013)
One of the important part in the process of construction of North Halmahera Regency Area is the determination of strategic planning for the improvement of the quality of the performance of such establishments. In carrying out or assisting the determination of planning-planning is still in the form of execution which is still done manually by the leadership of the party, thereby impeding the performance of these institutions a bit in determining the timing of the decision on the strategic planning decisions.Information technology can be used to assist in the improved performance of a business or organization. An organization that consists of a lot of people need to manage knowledge derived from these people through the process of knowledge management (KM).In this research will be applied the concept of knowledge management on strategic planning for the improvement of the quality of the performance of the agencies in North Halmahera Regency and applying methods of Analytical Hierarchy Process (AHP) to give advice in determining strategic planning decisions in development planning Congress (MUSRENBANG).